Hypoxia and growth factor profiling in high myopia: linking HIF-1α suppression and PDGF-BB activation to structural degeneration - Mérida, Salvador; García-Gen, Enrique; Desco, Carmen; Navea, Amparo; Bosch-Morell, Francisco (Frontiers in Medicine, 2025)
IntroductionHigh myopia is associated with structural and molecular changes in the eye, particularly involving hypoxia-responsive and fibrotic mediators. Growing evidence points to a subset of growth factors as central mediators of these alterations. Among these, our findings identify HIF-1α and PDGF-BB as key contributors to the progression of myopia.MethodsThis cross-sectional study included 88 Caucasian patients undergoing cataract surgery, categorized into control, low myopia, and high myopia groups based on axial length. Clinical assessments involved interferometric axial length measurement, swept-source OCT for choroidal thickness, and maculopathy classification following IMI guidelines. Aqueous humor samples were collected intraoperatively and analyzed using multiplex Quantibody arrays to quantify HIF-1α, VEGF, HGF, PDGF-BB, IL-6, and IL-17. Statistical analyses included Kruskal–Wallis tests with Bonferroni correction and correlation analyses to explore associations between molecular profiles and clinical severity.ResultsPatients with high myopia exhibited significantly reduced choroidal thickness and increased axial length (p < 0.01), along with a higher prevalence of degenerative maculopathy (71.9%). Molecular profiling revealed lower levels of HIF-1α and VEGF (p < 0.01), and elevated levels of PDGF-BB (p < 0.05), HGF, and IL-6 (p < 0.01) in the high myopia group. HIF-1α levels showed inverse correlations with disease severity, while PDGF-BB correlated positively with fibrotic markers. No significant differences were observed in IL-17 levels.DiscussionFor the first time, this study identifies significant alterations in HIF-1α and PDGF-BB levels in high myopia, with consistent correlations to key clinical parameters such as axial length, choroidal thickness, and maculopathy severity. These findings indicate an association suggesting a shift from adaptive hypoxia signaling toward fibrotic remodeling in high myopia. The suppression of HIF-1α and upregulation of PDGF-BB suggest a molecular imbalance that may be associated with structural degeneration. The integration of clinical imaging and aqueous humor profiling supports the potential of HIF-1α and PDGF-BB as biomarkers and therapeutic targets in pathological myopia.